Anteromedial cannulated screw fixation for Hawkins II/III talus fractures in children: a retrospective study - Xincheng Huang; Siyuan Ruan; Zhuolin Lei; Hong Cao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective To investigate the clinical effect of the anteromedial cannulated screw approach in the treatment of Hawkins II/III talus fractures in children. Methods A retrospective study was conducted on 20 children with talar fractures admitted to Renmin Hospital from September 2018 to February 2022. The fracture healing and functional recovery of the affected limb were strictly followed up after the operation. There were 14 males and 6 females. The average age was 9 years (range 6–12 years). According to the Hawkins classification, there were 12 cases of talar neck fracture type II and 8 cases of type III. All patients were fixed with cannulated compression screws via an anteromedial approach. According to the American Orthopedic Foot and Ankle Society ankle and hindfoot function scoring system, limb function was evaluated before and after the operation. A visual analog scale was used to evaluate the degree of postoperative pain. Results All 20 children were followed up for 12 months to 30 months, with an average of 15 months. We found that there was no significant difference in the excellent and good rate (76.9%) and necrosis rate (30.8%) between male children and female children (71.4%) and necrosis rate (28.6%) (P > 0.05). The excellent and good rates (92.9%) of children younger than 9 years old at the time of injury were higher than those of children older than 9 years old (33.3%), and the incidence of avascular necrosis of the talus was lower. The differences between the two groups were statistically significant (P < 0.05). The average prognosis score of children who underwent surgery within 5 days after injury was 89.2 ± 6.4, which was significantly higher than that of children who underwent surgery after 5 days (72.9 ± 13.1), and the difference was statistically significant (P < 0.05). There was no significant difference between patients who underwent surgery within 5 days after injury (15.4%) and those who underwent surgery after 5 days (51.7%) (P > 0.05). The excellent and good rates of talar neck fracture type II and talar neck fracture type III were 90.1% and 55.6%, respectively. Conclusion The anteromedial approach combined with cannulated compression screws for the treatment of Hawkins II/III talus fractures in children not only has a clear surgical field, but the fracture can also be reduced and fixed under direct vision using this technique. It does not affect the stability of the ankle joint and is conducive to the recovery of ankle function. It can be used as a surgical scheme for the treatment of talar fractures in children.